AINULINDALË, THE LORD OF THE RINGS AND LOTRO: ABOUT TIME - Martinez, Lis Yana de Lima (Abusões, 2019)
According to Physics (HAWKING, 2017), time originated at the Big Bang. According to some religions, time originated at the moment God created the universe. Arda’s time originated with the music sung by the Ainur and the counting of the days begun with Anar. In the following, I would like to offer a series of thoughts on the phenomenon of time comparing The Lord of The Rings Online (Lotro), released by Turbine Inc. and now maintained by Standing Stone Games, to Tolkien’s Arda. Also, I would like to introduce the idea that while time is originated both by the wonderful beings Ainur and Anar in the book, the player is the wonderful being that rules her/his own present time in Lotro. To do this, I proceed via a brief account of Stephen Hawking’s and game researchers’ considerations about time. I propose that even in their differences the dialogue established between the media (literature and video game) is successful. More specifically, I suggest that each medium has its particularities however from their dynamic dialogue fruitful intermediatic creations may emerge. According to Physics (HAWKING, 2017), time originated at the Big Bang. According to some religions, time originated at the moment God created the universe. Arda’s time originated with the music sung by the Ainur and the counting of the days begun with Anar. In the following, I would like to offer a series of thoughts on the phenomenon of time comparing The Lord of The Rings Online (Lotro), released by Turbine Inc. and now maintained by Standing Stone Games, to Tolkien’s Arda. Also, I would like to introduce the idea that while time is originated both by the wonderful beings Ainur and Anar in the book, the player is the wonderful being that rules her/his own present time in Lotro. To do this, I proceed via a brief account of Stephen Hawking’s and game researchers’ considerations about time. I propose that even in their differences the dialogue established between the media (literature and video game) is successful. More specifically, I suggest that each medium has its particularities however from their dynamic dialogue fruitful intermediatic creations may emerge.